(3JYdjbI Ydi efgL GdebGds - (3GdHgHgGfj, GdCUagGfj, GdaGQSj, eMeO HGbQ Hf eMeO Cced GdhMjO, J (B1205(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO (B... (3deG fHgJ acQj GdaGJQ Ydi JMbjbGJ aj GdQLGd(B...s
(3BNQgG (B:s
(3aQbI ef GdNWGHjI jbhdhf HCeGeI HRjY HYO CHj GdNWGH(B... (3eYGjfI CehGdge HcQI hYTjG(B. (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3, U(B154s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B350s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs